Isolation of avian pneumovirus in broiler chickens in Malaysia - Azri A. (2021)
A reverse-transcription polymerase chain reaction (RT-PCR), using oligonucleotide primer sets, was set up to detect the presence of avian pneumovirus (APV) associated with swollen head syndrome in broiler chickens. Three field isolates of APV, designated as AP4751/97, J4753/97, were confirmed by virus isolation in trachea organ culture (TOC) and RT-PCR.